Otomasi Rolling Door Menggunakan Android Dan QR Code - Angga Putra; Dwi Hadidjaja Rasjid Saputra (Jurnal Simetri Rekayasa, 2019)
Rolling Door is a door to protect items inside the room. In general, the locking system is still conventional by utilizing the key as a security system. The problem faced is the easy duplication of rolling door keys at this time. It is risky for others to open without the owner's knowledge, this design is done so that rolling doors have a more conventional level of security. The author tries to make a rolling door controller using the Android smartphone application and Arduino microcontroller via Bluetooth, in order to make it easier to use and replace the manual function by applying Bluetooth on an Android phone connected to the Bluetooth module on Arduino then the system is controlled via an Android handphone to send data to Arduino to be processed to control the condition of the motor, so that the rolling door can be opened and closed automatically using a solenoid door lock and QR Code as a lock.